Scheduling in modern conditions - Altukhova, D.; Tugay, O. (Ways to Improve Construction Efficiency, 2015)
The article describes the implementation of schedules in real terms, taking into account the variability of the production environment and the impact of various factors on the action plan. The author concludes that the use of fuzzy logic in the process of formation schedules and their adjustment is effective from the viewpoint of simplifying the process for their preparation and to save time.